Case series of rare ovarian malignancy: granulosa cell tumor - Duraisamy, Kavitha Yogini; Balasubramaniam, Devi; Chinnusamy, Palanivelu; Barnwal, Rashmi (International Journal of Research in Medical Sciences, 2017)
Granulosa cell tumors are rare ovarian sex cord stromal tumors characterized by indolent course and favorable prognosis. The treatment of granulosa cell tumor is individualized based on many factors like age, desire for future fertility and stage of the disease. Here, we report three cases out of which two were acute presentation and one was diagnosed incidentally when she got evaluated for menstrual irregularity. Fertility sparing surgery with proper staging is offered to young patients presenting in early stage. In patients who have completed family, comprehensive surgical staging including hysterectomy with bilateral salpingo oophorectomy is the standard treatment. Lymph node metastasis in granulosa cell tumor is very rare, hence pelvic and para aortic lymphadenectomy can be safely avoided if preoperative findings and frozen section favour granulosa cell tumor.